Acute-on-chronic liver disease enhances phenylephrine-induced endothelial nitric oxide release in rat mesenteric resistance arteries through enhanced PKA, PI3K/AKT and cGMP signalling pathways - Caracuel, Laura (Sci Rep, 2019)
Acute-on-chronic liver disease is a clinical syndrome characterized by decompensated liver fibrosis, portal hypertension and splanchnic hyperdynamic circulation. We aimed to determine whether the alpha-1 agonist phenylephrine (Phe) facilitates endothelial nitric oxide (NO) release by mesenteric resistance arteries (MRA) in rats subjected to an experimental microsurgical obstructive liver cholestasis model (LC). Sham-operated (SO) and LC rats were maintained for eight postoperative weeks. Phe-induced vasoconstriction (in the presence/absence of the NO synthase –NOS- inhibitor L-NAME) and vasodilator response to NO donor DEA-NO were analysed. Phe-induced NO release was determined in the presence/absence of either H89 (protein kinase –PK- A inhibitor) or LY 294002 (PI3K inhibitor). PKA and PKG activities, alpha-1 adrenoceptor, endothelial NOS (eNOS), PI3K, AKT and soluble guanylate cyclase (sGC) subunit expressions, as well as eNOS and AKT phosphorylation, were determined. The results show that LC blunted Phe-induced vasoconstriction, and enhanced DEA-NO-induced vasodilation. L-NAME increased the Phe-induced contraction largely in LC animals. The Phe-induced NO release was greater in MRA from LC animals. Both H89 and LY 294002 reduced NO release in LC. Alpha-1 adrenoceptor, eNOS, PI3K and AKT expressions were unchanged, but sGC subunit expression, eNOS and AKT phosphorylation and the activities of PKA and PKG were higher in MRA from LC animals. In summary, these mechanisms may help maintaining splanchnic vasodilation and hypotension observed in decompensated LC.